The Expression of hnRNP A2/B1 in Benign and Malignant Lung Lesions and Its Early Diagnosis Value in NSCLC. (5th October 2022) - Gu, Wenchao; Gao, Xiwen; Wang, Linxun; Deng, Guoping; Huang, Jiaru; Yang, Junxia; Liu, Yuan; Liu, Qun; Sang, Hongyang
Abstract : Lung cancer in its occurrence and development of different stages exist different biological behavior changes. This paper studies the expression of heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 in benign and malignant lung lesions and its early diagnosis value of nonsmall-cell lung cancer (NSCLC), aiming to provide reference for the early diagnosis and therapy of NSCLC. Some lung surgery specimens are selected from January 2021 to March 2022. All cases received no radiotherapy and chemotherapy before surgery, including 90 sufferers with benign lung lesions as the contrast set. hnRNP A2/B1 expressions are measured for comparison. The experimental results show that for lung cancer sufferers, the positive expression of hnRNP A2/B1 in their malignant lesion tissue is notoriously higher than that in their benign lesion tissue, and hnRNP A2/B1 is differently expressed in different differentiation and in different stages.